Detection of Dermacentor andersoni (Acari: Ixodidae) in Brazil on a Human Traveler Returning from the United States. Issue 2 (29th September 2020) - Faccini-Martínez, Álvaro A; Martins, Thiago F; Silveira, Iara; Labruna, Marcelo B
Abstract: Only one previous record of an exotic tick on a Brazilian traveler has been reported. Here, we report the detection of Dermacentor andersoni (Stiles) in Brazil while attached to a human traveler returning from the United States. This report is the fifth record of D. andersoni as an exotic tick, and the second record of an exotic tick on a South American traveler.